(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Semenov P.A. Keywords: animate category, complex approach, mentality, integrative approach. The review is devoted to the notion of animate category in Russian language. The author shows the historical development of the animate category in the Russian language on the material of written memorials. A complex integrative approach to the study of the animate category allows considering the history of animation category as the history of the meanings development in the context of the formation of the Eastern Slavic mentality.